The role of business analysis, ai-enabled insights, and data analytics in enhancing the efficiency of digital transformation in Saudi Arabian organisations - Hawsawi, Anwar; Alanizan, Salem (Edelweiss Applied Science and Technology, 2025)
The current research examines the pivotal role of business analysis, AI-powered insights, and data analytics in enhancing the effectiveness of digital transformation initiatives within Saudi Arabian organizations. The study provides context-specific information that is highly valuable to practitioners and policymakers, as it empirically substantiates the complex interactions among these factors. The findings highlight practical initiatives that organizations aiming to achieve successful outcomes from their digital investments and attain a long-term competitive advantage can implement. Although the cross-sectional design used in the quantitative analysis offers valuable insights, it limits the ability to draw definitive causal inferences. The results clearly demonstrate that business analysis, AI-enabled insights, and data analytics, individually, have a strong and positive impact on the successful delivery of digital transformation. Future academic research should consider incorporating longitudinal designs to capture the evolving dynamics of these relationships over time. Additionally, expanding the scope of investigation to include a broader range of nations and industries, as well as emerging technologies such as blockchain and generative AI, would significantly deepen the understanding of enablers of digital transformation.